Numerical simulation projects in micromagnetics with Jupyter - Lonsky, Martin; Lang, Martin; Holt, Samuel; Pathak, Swapneel Amit; Klause, Robin; Lo, Tzu-Hsiang; Beg, Marijan; Hoffmann, Axel; Fangohr, Hans (American journal of physics, 2024)
We report a case study where an existing materials science course was modified to include numerical simulation projects on the micromagnetic behavior of materials. The Ubermag micromagnetic simulation software package is used in order to solve problems computationally. The simulation software is controlled through the Python code in Jupyter notebooks. Our experience is that the self-paced problem-solving nature of the project work can facilitate a better in-depth exploration of the course contents. We discuss which aspects of the Ubermag and the project Jupyter ecosystem have been beneficial for the students' learning experience and which could be transferred to similar teaching activities in other subject areas. Editor's Note: Acquiring computational skills has become an important goal in STEM education. Computational literacy can be achieved through standard programming or numerical methods courses, but it can also be promoted in other courses, for instance through student projects. This paper describes this approach within the context of micromagnetics, making use of project Jupyter. The authors discuss how the Python-based open-source simulation software package they have developed facilitates student access to specialized numerical simulations. This paper should interest educators who try to implement numerical methods into their courses or labs.